2006
DOI: 10.1002/dvdy.20998
|View full text |Cite
|
Sign up to set email alerts
|

Start the clock! Circadian rhythms and development

Abstract: The contribution of timing cues from the environment to the coordination of early developmental processes is poorly understood. The day-night cycle represents one of the most important, regular environmental changes that animals are exposed to. A key adaptation that allows animals to anticipate daily environmental changes is the circadian clock. In this review, we aim to address when a light-regulated circadian clock first emerges during development and what its functions are at this early stage. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 145 publications
(179 reference statements)
0
62
0
Order By: Relevance
“…Biological rhythms such as in gene expression, physiology, and behavior have developed as a direct consequence of rhythmic sequences of light (day) and darkness (night) imposed by the rotation of the Earth (Menaker et al 1978;Dunlap 1999;Hardin 2005;Vallone et al 2007). As a rule, circadian rhythms (biological rhythms of approximately 24 h) persist, even in constant darkness, because they are controlled by an endogenous mechanism known as the "biological clock" (Helfrich-Förster 2002).…”
Section: Circadian Plasticity As a New Type Of Neuronal Plasticitymentioning
confidence: 99%
“…Biological rhythms such as in gene expression, physiology, and behavior have developed as a direct consequence of rhythmic sequences of light (day) and darkness (night) imposed by the rotation of the Earth (Menaker et al 1978;Dunlap 1999;Hardin 2005;Vallone et al 2007). As a rule, circadian rhythms (biological rhythms of approximately 24 h) persist, even in constant darkness, because they are controlled by an endogenous mechanism known as the "biological clock" (Helfrich-Förster 2002).…”
Section: Circadian Plasticity As a New Type Of Neuronal Plasticitymentioning
confidence: 99%
“…Rhythms of cell proliferation are evident from cyanobacteria to humans (Bjarnason & Jordan 2000, Mori & Johnson 2000, and several cell cycle genes have been shown to be under transcriptional control by circadian clock factors (Reddy et al 2005, Hunt & Sassone-Corsi 2007, Vallone et al 2007. Our recent study in zebrafish larvae has indicated a role for glucocorticoids in the regulation of these rhythms (Dickmeis et al 2007). Circadian cell cycle rhythms are present both in the larvae and in zebrafish-derived cell lines, implying a cell-autonomous clock regulation also in this species (Dekens et al 2003).…”
Section: Glucocorticoids and Circadian Cell Cycle Rhythmsmentioning
confidence: 99%
“…Circadian cell cycle rhythms are present both in the larvae and in zebrafish-derived cell lines, implying a cell-autonomous clock regulation also in this species (Dekens et al 2003). However, the examination of pituitary mutant larvae revealed that, in vivo, the rhythms depend on systemic input from this gland (Dickmeis et al 2007). Analysis of mutants with overlapping pituitary cell type deficiencies pinpointed the corticotrope lineage as the source for the required signal.…”
Section: Glucocorticoids and Circadian Cell Cycle Rhythmsmentioning
confidence: 99%
“…Is circadian amplitude in gene expression affected by growth conditions? This topic of early circadian rhythmicity has been recently reviewed (Vallone et al, 2007). In mammals, the fetal clock is synchronized with the outside environment by maternal signals (Reppert and Schwartz, 1983;Reppert, 1995).…”
mentioning
confidence: 99%